FAIRCLOUGHFIANS SFL ANALYSIS OF ARABIC DISCOURSE - Haryono, Abdullah; Al Farisi, Mohamad Zaka; Supriadi, Rinaldi (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2025)
Arabic-language podcasts can play a significant role in shaping netizens’ perceptions of social norms, including language's role as a tool of communication, as they serve as a primary source of knowledge and cultural values. This study seeks to fill this gap by applying Fairclough's Critical Discourse Analysis to an Arabic podcast. The analysis employs a Systemic Functional Linguistics approach drawing on Norman Fairclough's three-dimensional framework: textual analysis, discursive practice, and social practice. Data were collected from public comments on social media platforms and analyzed to identify linguistic patterns, discourse strategies, and the construction of ideology and cultural identity. By examining the podcast channel comment section, the findings highlight the importance of advancing critical sociolinguistic studies in the digital sphere, particularly within the context of Indonesia–Arab interactions, and open opportunities for broader research across other online platforms and communities